Cover Feature: Highly Sensitive Method to Isolate Photocurrent Signals from Large Background Redox Currents on Protein‐Modified Electrodes (ChemElectroChem 11/2019). Issue 11 (2nd May 2019) - Jun, Daniel; Beatty, J. Thomas; Bizzotto, Dan
Abstract : The Cover Feature illustrates an amplitude modulated approach for measuring photocurrent signals ( i PC ) originating from reaction center proteins bound to a gold surface at any applied potential. This approach uses a modulated light intensity signal and a lock‐in amplifier to isolate small photocurrents from large background currents ( i DC ) due to the redox of the hydroquinone (HQ) sacrificial donor on the uncovered electrode surface. More information can be found in the Article by D. Jun et al. on page 2870 in Issue 11, 2019 (DOI: 10.1002/celc.201900249 ).